Researching hidden populations: approaches to and methodologies for generating data on trafficking in persons - Kangaspunta, Kristiina (Forum on crime and society)
This issue of the United Nations Office on Drugs and Crime journal Forum on Crime and Society focuses on research related to trafficking in persons. It contains articles by a range of researchers and academics with experience in identifying 'hidden populations' such as trafficking victims. The articles present research methods and approaches that have been used with success to uncover 'hidden populations' in different contexts in the past. It is hoped that this edition of the Forum will stimulate the generation of more sound data on the different aspects of trafficking in persons worldwide.